Henry Hunter Calvert's collection of amphora stamps and that of Sidney Smith Saunders - Johnston, A. W. (Archaeopress Archaeology, 2020)
Henry Hunter Calvert was a British consul in Alexandria from 1857 to 1882, at which date he and many others fled from the riots in the city. The consulate was sacked, destroying Calvert's collections, but an annotated list of the Greek amphora stamps had been sent to the British Museum, published here for the first time.